Setting policy on asylum: Has the EU got it right? - Tim Hatton (IZA World of Labor, 2015)
Policy toward asylum-seekers has been controversial. Since the late 1990s, the EU has been developing a Common European Asylum System, but without clearly identifying the basis for cooperation. Providing a safe haven for refugees can be seen as a public good and this provides the rationale for policy coordination between governments. But where the volume of applications differs widely across countries, policy harmonization is not sufficient. Burden-sharing measures are needed as well, in order to achieve an optimal distribution of refugees across member states. Such policies are economically desirable and are more politically feasible than is sometimes believed.
Keywords: I15; J11; J61; N33; N34; N37; 330; asylum; asylum-seekers; Common European Asylum System; policy harmonization